Local governance of critical infrastructure resilience: Types of coordination in German cities. (23rd November 2021) - Knodt, Michèle; Fraune, Cornelia; Engel, Alice
Abstract: The resilience of critical infrastructures in cities is key to being prepared for future crises. The challenge of enhancing critical infrastructure resilience addresses a multitude of actors. However, we lack conceptual, as well as empirical, understanding of how these different actors are coordinated. Therefore, this contribution asks how the different actors involved in critical infrastructure governance are coordinated at the local level. With the help of a typology of network governance coordination (political leadership, mutual exchange, and positive coordination), we look at the critical infrastructure crisis management in major German cities based on survey data with the scenario of a long‐lasting, supraregional power outage. The results show that political leadership coordination, as a unilateral and information‐based way of addressing public and private actors, is the dominant type. Only a quarter of the cities have chosen measures of mutual exchange coordination based on the consultation in an ad hoc manner. Measures of positive coordination where institutionalized joint planning is central are taken up only by a minority of German cities. Assuming that positive coordination is particularly important in dealing with unexpected events, positive coordination emerges as the missing piece of the resilience puzzle for many German cities.